NGHIÊN CỨU SỬ DỤNG POLYME IN DẤU PHÂN TỬ TRÊN CÁC CHẤM LƯỢNG TỬ CARBON LÀM CẢM BIẾN HUỲNH QUANG XÁC ĐỊNH NAPROXEN - Nguyễn, Đình Thi; Trần, Đông Dương; Trần, Ngọc Bích; Phạm, Thị Ngọc Mai (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON USING MOLECULAR IMPRINTING POLYMER ON CARBON QUANTUM DOTS AS OPTICAL SENSOR FOR DETERMINATION OF NAPROXENIn this study, CQDs-SiO2@MIP fluorescence sensor was fabricated via sol-gel polymerization using naproxen as the template molecule, carbon quantum dots (CQDs) as the signal materials, 3-aminopropyltriethoxysilane (APTES) as the functional monomer, and tetraethylorthosilicate (TEOS) as the cross-linker. The specific recognition sites in the polymer layers could selectively adsorb naproxen molecules, which caused fluorescence-quenching behavior of CQDs via an electron transfer process. The CQDs-SiO2@MIP system can detect naproxen in aqueous solution (pH 4.0; Acetate buffer 0.04M) sensitively (ppb level) with a response time of 15 min. The results show that the fluorescence recovery has a good linear relationship with Naproxen concentration in the range of 10-7 M to 1.5 10-7 M. Method has very low limit of detection (LOD) of 5 10-8M (11 ppb), limit of quantitation (LOQ) of 1.5 10-7M (34 ppb), high accuracy (recoveries > 96%) and high precision (RSD < 3%). Method has high selectivity over various substances such as K+, Mg2+, Ca2+, Zn2+, glucose, piroxicam, acid mefenamic,… The developed method was successfully applied for determination of naproxen in pharmaceutical samples. Good agreement between results of our method and LC-MS/MS method suggest that fluorescence is a reliable and cost-effective method for naproxen determination.